Influence of strength of lower extremities on performance succsess on floor exercise - Paunovic, M.; Velickovic, S.; Curovic, M.; Okicic, T.; Antic, V.; Milocevic, N.; Ostojic, S. (Book of Proceedings Fis Communications 2019, 2019)
The aim of the study was to determine the influence of strength of lower extremities on performance succsess on floor exercise with young gymnasts. The sample of respondents for this research consisted of 20 top gymnasts from eight countries (Austria, Bosnia and Herzegovina, Bulgaria, Russia, Slovenia, Serbia, Croatia and Switzerland), aged 14 to 16 years, three to 10 years of training (average 6.9) and body weight from 31kg to 58kg (average weight 43.52kg). IMADAZ2H-1100 Japanese Digital Dynamometer with WinWedge 3.4 software was used to evaluate the absolute and relative strength of the lower extremity muscles. And for further statistical analysis the results from the competition were taken ("D" and "E" score, and the sum of "D" and "E" scores were taken as final score).Descriptive statistics and regression analysis were used for all variables to determine the influence of muscle force on competition score. The results of the regression analysis showed that there is no statistically significant influence of lower extremity strength on the performance success on floor exercise with gymnasts. The results of this research can provide useful guidance and serve as an adequate basis for further research in artistic gymnastics.